Enhancing Employee Retention in Modern Shopping Centers: The Impact of Training and Job Design in Surabaya: Meningkatkan Retensi Karyawan di Pusat Perbelanjaan Modern: Dampak Pelatihan dan Desain Pekerjaan di Surabaya - Novianto, Iful; Rizqiawan, Hendrik; Indrawati, Trisa (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study examines the influence of training and job design on employee retention in modern shopping centers in Surabaya. The analysis of 35 experienced respondents reveals that both training and job design are highly valued factors, with average scores above 3.25. Job design particularly stands out with an average score of 3.51. Regression analysis confirms that both training and job design significantly impact employee retention, emphasizing their crucial role in supporting employee performance and retaining valuable workforce in the retail industry. This research aligns with previous studies highlighting the positive correlation between training and employee retention, as well as the impact of job design on retention in other organizational settings. The findings offer valuable insights for HR practitioners and decision-makers aiming to enhance employee retention strategies in modern shopping centers. Highlight: mportance of Training and Job Design: The study emphasizes the significance of providing appropriate training and favorable job design to employees working in modern shopping centers, as these factors are considered crucial for enhancing employee retention. Quantitative Approach: The research adopts a quantitative approach, employing descriptive and regression analyses, to explore the relationship between training, job design, and employee retention in Surabaya's modern shopping centers. Significant Impact: Findings reveal that both training and job design have a significant effect on employee retention, as perceived by employees, underscoring their role in retaining skilled workforce within the retail industry. Keyword: Employee Retention, Training, Job Design, Modern Shopping Centers, Surabaya